Accurate dosimetry for microbeam radiation therapy - DIMITRI REYNARD (2019)
Microbeam Radiation Therapy (MRT) is an emergent treatment modality that uses spatially fractionated synchrotron x-ray beams. MRT has been identiﬁed as a promising treatment concept that might be applied to patients with malignant cen-tral nervous system (CNS) tumors for whom, at the current stage of development, no satisfactory therapy is available yet. The use of a fractionated beam allows a better skin sparing and a better tolerance of healthy tissue to high dose rates. MRT consists of a stereotactic irradiation with highly collimated, quasi-parallel array of narrow beams 50 µm wide spaced with 400 µm made of synchrotron generated x-rays at an energy ranging from 0 to 600 keV. The European Synchrotron Radiation Facility (ESRF) as an x-ray source allows a very small beam divergence and an extremely high dose rate. The dose deposited on the path of the primary photons (peak dose) of several hundred grays (Gy) is well tolerated by normal tissues and provides at the same time a higher therapeutic index for various tumor models in rodents. The high dose rate forces us to develop an accurate and reproducible dosimetry protocol to ensure the matching between the prescribed and the deliv-ered dose. MRT is by deﬁnition a non-conventional irradiation method, therefore the number of dosimetric errors becomes larger than in conventional treatments due to two reasons (i) the reference conditions recommended by the Association of Physicists in Medicine (AAPM) or the International Atomic Energy Agency (IAEA) cannot be established, (ii) the measurement of absorbed dose to water in composite ﬁelds is not standardized.This PhD is focused on bridging the gap between MC simulated values of output fac-tors (OF) and peak-to-valley dose ratios (PVDR) and experimental measurements. Several aspects of the irradiation setup such as insertion devices on the path of the x-ray beam are accounted for as well as the internal structure of the dosimeters. Each contribution to OF and PVDR is quantiﬁed to correct for the measurements.